BMI and psychological distress in 68, 000 Swedish adults: a weak association when controlling for an age-gender combination - Brandheim Susanne; Rantakeisu Ulla; Starrin Bengt (BMC, 2013)
Abstract Background Study results concerning associations between body mass index (BMI) and psychological distress are conflicting. The purpose of this study was to describe the shape of the association between BMI and psychological distress in a large sample of Swedish adults. Methods Data was measured with the General Health Questionnaire-12 (GHQ-12), in 68,311 adults aged 18-74. Self-reported data was derived from a merger of the 2000, 2004 and 2008 Life and Health (Liv och Hälsa) questionnaires focusing general perceived distress as well as living conditions. Logistic regression analysis was used to describe the association between BMI and psychological distress when controlled for age and gender in combination. Results Women reported an overall higher psychological distress than men. A significant pattern of decreasing psychological distress with increasing age emerged among women in all BMI categories. Trends of this same pattern showed for men. Small or no differences were seen in psychological distress between those in normal weight, overweight, and obesity I categories (among women: 20.4%, 18.4%, 20.5%; among men: 12.8%, 11.2%, 12.9%). For both genders, any notable increase in psychological distress appeared first in the obesity II category (among women: 27.2%. Among men: 17.8%). Conclusions Psychological distress decreases with increasing age regardless of BMI; a pattern more obvious for women. Being categorized with obesity II leads to a markedly higher psychological distress than being categorized with normal weight, overweight or obesity I. From this, we suggest that future obesity research focusing on psychological distress could investigate the role of stigma and norm susceptibility in relationships where people are evaluated through the eyes of the other.